Seedling and sapling banks as sources of resilience in plant communities subjected to land use change in central Argentina semiarid forests - Lipoma, María L. (2016)
Fil: Lipoma, María L. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.